Vietnamese Students’ Perception and Loyalty towards an Image of Vocational Education and Training - Dang, Vi Hoang (Journal of Education and Vocational Research, 2014)
Stakeholders’ perceptions towards a career in vocational education and training (VET) in Vietnam negate the country’s industrial development plan. During the last 15 years, the Vietnamese Governments investment in to the sector increased annually. However, parents and their children still pursue the goal of higher education via the mainstream rather than a career path way using the vocational education and training system. Although stereotypical views of vocational students are being challenged, Confucian ideology maintains some influence over stakeholders’ educational decisions leading to the sustained popularity of higher education. This study explores the perceptions of students on the image of and their loyalty towards vocational education and training. A sample of 300 lower secondary school, 300 upper secondary school, and 300 vocational students was drawn from across the Northern and Southern regions of Vietnam. A survey questionnaire was used to collect data and mean analysis conducted to explore the data. The findings indicate that agreement with statements about facilities and equipment, teacher’s ability, curriculum, and soft skills are the clearest indicators of enhanced perceptions about the image of vocational education and training. Encouragement from parents appears most influential to positively affecting lower secondary students’ loyalty. Unexpected was that vocational students had less interesting continuing in vocational education and training compared to lower and upper secondary school students inclination towards a career in VET. First-hand experience seemingly leads to diminished perceptions and loyalty towards vocational education.